A Systematic Review of the Validity of Questionnaires in Second Language Research - Yifan Zhang; Vahid Aryadoust (MDPI AG, 2022)
Questionnaires have been widely used in second language (L2) research. To examine the accuracy and trustworthiness of research that uses questionnaires, it is necessary to examine the validity of questionnaires before drawing conclusions or conducting further analysis based on the data collected. To determine the validity of questionnaires that have been investigated in previous L2 research, we adopted the argument-based validation framework to conduct a systematic review. Due to the extensive nature of the extant questionnaire-based research, only the most recent literature, that is, research in 2020, was included in this review. A total of 118 questionnaire-based L2 studies published in 2020 were identified, coded, and analyzed. The findings showed that the validity of the questionnaires in the studies was not satisfactory. In terms of the validity inferences for the questionnaires, we found that (1) the evaluation inference was not supported by psychometric evidence in 41.52% of the studies; (2) the generalization inference was not supported by statistical evidence in 44.07% of the studies; and (3) the explanation inference was not supported by any evidence in 65.25% of the studies, indicating the need for more rigorous validation procedures for questionnaire development and use in future research. We provide suggestions for the validation of questionnaires.